IDENTIFIKASI ARSITEKTUR TROPIS PADA BANGUNAN LAMA DI JALAN SITI KHADIJAH KOTA BENGKULU - Fitrianty Wardhani; Dwi Oktavallyan (ATRIUM: Jurnal Arsitektur, 2019)
Title: Identify tropical architecture in the old building at Jalan Siti Khadijah Bengkulu City Tropical architecture tries to deal with the tropical climate problems characterized by heavy rain, blazing sun, high air temperatures, high humidity (for humid tropics), and low wind speeds. The realization of a sustainable tropical city requires building environmentally responsive designs. The efforts could be made, such as selecting materials and models on buildings' external and internal appearance that suit to tropical city. Old buildings used to be built to adapt to the local climate. One of them is the old buildings on Khadijah street, which the existence is almost gone now. This study aims to identify the tropics element in old buildings that have adapted to the tropical climate. The method used in this research is a qualitative descriptive method in case studies through observation and identification of the application of tropical architectural elements in the external appearance (building and roof orientation) and the internal appearance in the building (space, floor, wall, and opening patterns). The aim of this research is to fulfill the arguments for the community about the significance of maintaining the old buildings. This finding is needed to provide a logical reason for the community and government to conserve the old buildings in Bengkulu City.